Hire purchase controls and replacement cycles - GHANDHI, J.K.S. (PSL Quarterly Review, 2014)
The control of hire purchase by specifying and altering minimum terms has been subjected to numerous objections, most of which are administrative or social in substance. Recently, however, a strictly economic critique of these controls has been developed which contends that hire purchase controls tend to lead to replacement cycles in the market for consumer durables. The present article tests this hypothesis by formalizing the basic model and testing it with empirical data. Based on the analysis and the statistical evidence the author argues that the conditions necessary for the generation of a hire purchase induced replacement cycle are unlikely to be realized, except in the most extreme circumstances. Therefore, the objection to the use of hire purchase controls on the grounds that they tend to lead to replacement cycles is unwarranted. JEL: D12, L68